Adopting a healthy lifestyle: it’s a choice - Muhammad Imran Kadir; Nurul Syafiqah Zambri; Nurul Adilla Mohd Yunus; Nurul Husna Abdul Halim (2023)
A healthy lifestyle is one of the ways a person needs to live in order to achieve their optimal health including physical, mental, and social well-being. Researchers have shifted their focus to awareness of the importance of adopting a healthy lifestyle practice among communities. This is due to health issues that have arisen recently among communities that have become a public concern. The objective of this study is to investigate the relationship between peer influence, heredity disease and mental well-being in adopting a Healthy Lifestyle practice among communities in Malaysia. 384 respondents participated in this study which was conducted through Whatsapp, Facebook, and Instagram. This study focused on generation Z, a disease suffered and all Malaysians. The result showed that peer influence, heredity disease and mental well-being influence communities to adopt a healthy lifestyle.